Examination of OH and H2O2 production by uniform and non-uniform modes of dielectric barrier discharge in He/air mixture. (1st December 2022) - Yatom, Shurik; Dobrynin, Danil
Abstract: In this work we have carried out a parametrical study of hydroxyl radical (OH) generation in nanosecond dielectric barrier discharge (DBD) in He/air mixture using a laser-induced fluorescence approach. The foci of the study are the investigation of differences between uniform and non-uniform modes of the discharges and the difference in production of OH and H2 O2 Nanosecond-time scale imaging of the discharge shows transition from streamer to diffuse mode when applied electric field to the discharge gap approaches ∼90 kV cm −1 . The results show that both OH production in the gas phase and downstream H2 O2 delivery rates to liquid depend on the discharge mode operation and are respectively 30% and 3 times higher for the non-uniform DBD compared to the diffuse discharge.